Copper−iron dimer for selective C–C coupling in electrochemical CO2 reduction. (1st June 2021) - Xie, Heping; Wang, Fuhuan; Liu, Tao; Wu, Yifan; Lan, Cheng; Chen, Bingbing; Zhou, Jianqiu; Chen, Bin
Abstract: The electrochemical CO2 reduction to fuels and chemicals using renewable electricity provides a promising strategy for resolving energy environmental crisis and achieving carbon neutral. Progress has been made on catalyst design for CO2 conversion to high valued products. However, the efficient production of multi−carbon compounds is very challenging due to low selectivity and high overpotential. Understanding of catalytic mechanism at the atom level is the key to developing high−performance CO2 reduction catalysts. Herein, employing comprehensive density functional theory computations, we systematically investigated the structures, reaction intermediates, CO2 reduction mechanisms, and the selectivity of state−of−art catalysts—heteronuclear CuFe dimers anchored on nitrogenated carbon monolayers as the CO2 reduction electrocatalysts. The results show that the strong binding between cooperative CuFe dimer and nitrogenated carbon matrix not only prevents the metal from clustering but also dictates favorable electronic structures, that explains their superior CO2 reduction activity, high C2 H5 OH selectivity and the mechanism of hydrogen evolution inhibition. Graphical abstract: Image, graphical abstract